Analisis Semiotik Pada Kain Ulos Suku Batak - Lubis, Anita Angraini; Nasution, Rahma; Hasibuan, Sahid Fadhil; Khiria, Linny (Jurnal Hata Poda, 2023)
This research focuses on the analysis and interpretation of the values and meanings contained in Ulos cloth, as identity and culture. The aim of this research is to understand the meaning implicit in Ulos cloth culture. To limit understanding, the researcher formulated the research focus in a simple description with several core points contained in the title Culture and Characteristics of the Batak Tribe. Data collection techniques were carried out through observation and interviews. This research uses qualitative research methods. By using this method we find out the meaning contained in Kian Ulos as Batak Culture. The purpose of this research is to find out the philosophical meaning contained in the Ulos Cloth, to find out the message contained in the Ulos Cloth. Keywords: Culture, Semiotic Analysis, Meaning contained in Ulos Cloth.